Unseen shadows: exploring the impacts of stalking on female college students’ lives, health, and relationships in Sindh - Hadi, Abdul; Snoubar, Yaser (Frontiers in Psychology, 2025)
IntroductionStalking is a serious and often overlooked form of gender-based violence that disproportionately affects adolescent girls. In Pakistan, especially in Sindh, the issue remains under-researched, despite legal reforms aimed at criminalizing such behaviors.MethodsThis study employed Interpretative Phenomenological Analysis (IPA) to explore the lived experiences of 20 adolescent female stalking victims aged 15–17 at a co-educational college in Sindh. Data were collected through semi-structured interviews.ResultsTwo major themes emerged: (1) the victim-stalker relationship and stalkers’ motivations, and (2) the psychological, social, academic, and financial impacts of stalking. Most stalkers were strangers who sought unwanted intimacy. The victims experienced fear, social isolation, stigma, academic disruption, and in some cases, long-term psychological trauma including hallucinations and clinical depression. Cultural norms and institutional apathy further silenced victims and exacerbated their vulnerability.DiscussionFindings highlight the urgent need for gender-sensitive training for formal institutions, public awareness campaigns, and victim-centered interventions. Policymakers must recognize stalking as both a criminal and public health concern, particularly in patriarchal settings where girls’ autonomy is routinely compromised.